ANALISIS NETRALITAS MEDIA TELEVISI DALAM DEBAT PILPRES 2019 - Soelistyawati, Rr Dinar (Jurnal Ilmu Komunikasi AKRAB, 2019)
ABSTRACTCommunication in this dynamic era makes us to be critical in responding every talkings. Along with taht, the critical manner in communication is needed in almost of all levels, statrs from the intrapersonal level tothe organizational level, as well as on the social field, include in political field such as 2019 Presidential Election and 2019 Presidential Debate. This research?s aims are to analyze the attempt of television station in prioritize neutrality when airing the news about 2019 Presidential Debate also analyzing the citizen?s behaviour and mindset in responding the news about it. This will discuss about the euphoria of 2019 Presidential Debate, how are television stations implementing their neutrality in airing it, how it interpreted into the air with ways of the neutral and the anti-neutral ones, also the citizen?s behaviour and mindsets against the anti-neutral news of it. This qualitative research is using the mixed theories between the social responsiility of media and framing theory to analyze the television?s involvement as political communication media in giving their interpretations about 2019 Presidential Debate to the citizen, whether it is aired wtih the way of prioritize the neutrality or not. The result of this research shows that the implementation of television broadcasting based on the neutrality one with the anti-neutral one can giving the variation of citizen?s mindset so to intepreting those mindsets, deeper and holistic identification is needed to analyze the meaning of those information so can create a good prediction to the citizen for the growth of the country in the next five years.Keywords: Media Neutrality Analysis, Television, 2019 Presidential Debate